USING ARTIFICIAL INTELLIGENCE TO ASSESS AND PREDICT SKILLS IN THE LABOR MARKET - Mariia Gogoleva (American Journals, 2025)
In the current context of developing artificial intelligence (AI) technologies, the role of worker skills in the labor market is undergoing significant transformation. This article explores ways to apply AI methods to assess current professional skills and forecast their future demand. Based on a literature review, recommendations are offered for stakeholders: employers, educational institutions, and public policy agencies.
Keywords: Artificial intelligence, skills assessment, demand forecasting, labor market, AI literacy, skills of the future, machine learning.